Exploring Efficacy - Maryam, Rini; Irianto, Sulistyowati (Lentera Hukum, 2023)
The rising global divorce rate is reshaping the landscape of family dispute resolution, moving away from the adversarial or litigation system toward an alternative dispute resolution known as mediation. This global trend is also observed in Indonesia where the Supreme Court has mandated the use of mediation in civil cases. "Everybody wins, nobody loses" as the primary slogan of mediation emphasizes a win-win outcome for all parties involved, avoiding any losers. However, assessing its efficacy in handling divorce cases in Indonesia becomes crucial. This is mainly because the settlement rate has been discovered to be low in Indonesia since the mandatory implementation of court-annexed mediation for almost two decades compared to other countries such as Australia and the United States. In both countries, settlement is not only based on agreements but also on the process that satisfies the parties. Therefore, this study aims to examine the conceptual issues underlying the low effectiveness of divorce mediation by questioning agreements as a measure of divorce mediation effectiveness. This study uses the sociolegal framework to critique the Supreme Court Regulation 1/2016 regarding Mediation in court and its dynamics in divorce cases. Moreover, courtroom study is applied to observe the mediation process. The results showed that the success of mediation revolves around the number of agreements reached by the parties and the process did not focus on the characteristics of divorce cases, thereby considered not suitable for all cases. Furthermore, the court-annexed mediation regulation creates ambiguity between the use of marital mediation to reconcile the parties and divorce mediation to proceed post-divorce agreement or both.Keywords: Effectiveness of Mediation, Divorce Mediation, Religious Courts.